Empregos verdes : estratégia de promoção de oportunidades de emprego, trabalho decente e sustentabilidade ambiental - Marini, Rosane Sandoval Gonçalves (2014)
This review presents some aspects of the Green Jobs initiative, an topic which is the result of researches conducted within the International Labour Organization - ILO and its leading challenge is associating the dynamism of decent labor supply in a sustainable economy, policy that will only be achieved with the policies of quenching of the climate change, which affects all countries, accelerates environmental degradation and compromises the quality of life even as the promotion of decent work. This target is justified because the increase in productivity and increasing competitiveness, derived from a scenario of economic globalization, not only end up compromising the quality of life in the workplace, but also the aggravation of the environmental issue, due to the misuse of natural resources, so as to form a cycle of social and environmental damage. For this, it is analyzed the balanced work environment as decent work component, as well as it evaluates green jobs through the view of sustainable development in its three dimensions: economic, social and environmental, essential pillars for the economic reactivation world and the creation of decent work. In this context, it is understood that the adoption of more efficient production and consumption and less destructive environmental point of view models are able to create opportunities to reduce poverty, bring forth decent work and promote social dialogue, transformation, however, that depends on a firm and coherent structure in terms of public policies, even as the involvement of key stakeholders: employers, workers and governments.